A Narrative Review on the Role of Yoga on Polycystic Ovary Syndrome: Life Sciences-Ayurveda - Mirase, Janhvi; Kuchewar, Vaishali; Parwe, Shweta (International Journal of Life Science and Pharma Research, 2023)
PCOS is an endocrine condition affecting women of reproductive age. It is connected to a specific style of life. If treatment is put off, it lowers fertility and may result in serious new problems. The precise origin of polycystic ovarian syndrome is unknown because it is believed to be a complex metabolic disorder. It demonstrates infertility, obesity, hirsutism, acne, and menstrual disorders specifically. PCOS is treated based on how it presents clinically at different phases of life. Women with polycystic ovarian syndrome reported feeling more anxious than women in good health. The estimated range for PCOS prevalence worldwide is 6-26%. Depending on the menstrual, androgen, and infertility clinical characteristics, a therapeutic strategy is chosen. Current medical practises are unsatisfactory. For polycystic ovarian syndrome, alternative therapies are helpful, including herbal medicine, a nutritious diet, lifestyle changes, exercise, yoga, and techniques for reducing stress. A key component of PCOS treatment is lifestyle management. The best way to change one’s lifestyle is to adopt yoga. Through the establishment of homeostasis, yoga helps the individual become healthy. The eight-limbed path of Ashtanga yoga promotes psycho-somatic equilibrium. At present, yoga, entails physical postures called asanas, breathing exercises called pranayam, and meditation called dhyana (Meditation). Yoga has the potential to be both preventative and curative, according to scientific data. It works well as a supportive treatment for PCOS patients to enhance their quality of life. Thus, the focus of this review is on defining the function of yoga in the treatment of PCOS. This review included all of the studies that looked at the impact of yoga on PCOS patients. Data search revealed substantially less literature on yoga and PCOS, although the six original studies indicated support for yoga’s importance in PCOS management. It has an impact on overtly contributory factors such stress, insulin resistance, and obesity.